Perlukah Pekerja Migran Indonesia Dilindungi? - Anggriani, Riri; Arfanita, Arfanita (Universitas Widya Gama Malang, 2024)
The provincial government has the duty and responsibility to protect Indonesian migrant workers (PMI), especially those from their respective regions. This research is very important because the provincial government is the main determinant of improving PMI protection governance in their area. Protection of PMI is needed because PMI continues to experience various problems, including illness in the country of placement, the period of stay and work permits having expired, experiencing abuse, unpaid wages, migrant workers being pressured to pay compensation from the departing agent, leaving illegally, working without wages, victims of termination of employment, not having placement agreements and work agreements, being recruited illegally, not having complete documents, and not receiving job training. This study aims to determine the duties and responsibilities of the Regional Government of Central Sulawesi Province in protecting migrant workers in their area. The research method used is empirical legal research, starting with the stages of literature study, data collection, interviews, and legal analysis. The results of the study show that the Regional Government of Central Sulawesi Province has carried out its duties and responsibilities to protect PMI. However, of the nine obligations mandated by the PMI protection law, the Regional Government of Central Sulawesi Province still has two that have not been fulfilled, namely: point a) organizing education and job training by accredited government and/or private educational institutions and job training institutions; and point g) providing and facilitating training for PMI candidates through vocational training, whose budget comes from the education function. This is constrained by limited local budgets. Regional funding is more focused on public health as a result of the COVID-19 pandemic and still relies on data from BP2MI.